PERHITUNGAN STANDARD MINUTE VALUE (SMV) JAS LABORATORIUM DENGAN METODE PRE-DETERMINED MOTION TIME SYSTEM (PMTS) - Dini, Faiz Fajar (Texere, 2025)
The success of a sewing line in producing a garment product can be measured by its achievement on targets, production efficiency, product quality, and delivery on time. In calculation of production targets and efficiency accurately need SMV (Standard Minute Value) or SAM (Standard Allowed Minute) as the standard time commonly used by the garment industry in calculating production targets, efficiency, production costs, labor costs, and line balancing. This research aims to find out the SMV of laboratory coats using the Pre-Determined Motion Time System (PMTS) method by (General Sewing Time) GST software. To obtain SMV, the process carried out are breakdown processes of the laboratory coat and analyzing the motions of each operation to identify the motion codes specified in GST. GST calculation generated 40.02 minutes for SMV of laboratory coats.